Availability and suitability of Kuala Gula mangroves for milky stork reintroduction program in Malaysia: a re-evaluation - Abdul Rahman, Mohd Faid; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
The Milky Stork population is endemic to a small part of the Southeast Asia region and is considered as an endangered species as its number has gone considerably low throughout its home-range. In Malaysia alone, the species numbers have dwindled significantly and the last group of the wild population was last recorded in 2010. Hence, the work to repopulate the species is currently being done in Kuala Gula, Perak as the location is still considered as pristine and of high importance to large numbers of resident and migratory birds. However, the recent increase of anthropogenic activity in the area has raised considerable attention among environmentalist and scientist as the mangroves along Kuala Gula coast are being reclaimed excessively to give way to the aquaculture industry. Accordingly, this study was undertaken to re-evaluate the availability and suitability of Kuala Gula as nesting and foraging grounds for the reintroduction of the Milky Stork population. Important nesting and foraging areas were surveyed and data on the habitat, including size, types, forest composition and structure were recorded. In general, at least one nesting site and two foraging areas have been affected and could no longer benefit the waterbirds population. The findings suggest that urgent attention be given to protect remaining mangroves from further development and reclamation activity to ensure the success of the reintroduction program in the future.